Comparisons between the antioxidant activities of the extracts of anacardium occidentale and piper betle - Mokhtar, Nur Masitah; Kanthimathi, M.S.; Aziz, Azlina Abdul (2008)
In this study, the antioxidant capacities of extracts of Anacardium occidentale were compared with those of Piper betle. Antioxidant activities were evaluated based on their ability to reduce ferric ions and scavenge DPPH·, ABTS·+ and nitric oxide radicals. Total phenolic content of these plants were measured by the Folin-Ciocalteau method. The plants were extracted with methanol, ethyl acetate and hexane. With the exception of the ethyl acetate and hexane extracts of A. occidentale, the other extracts showed significant radical scavenging and reducing properties. The ethyl acetate extract of P. betle contained the highest total phenolic content, showed the highest ferric reducing and DPPH· scavenging activities. However, the methanol extract of A. occidentale was potent at scavenging the ABTS·+ and nitric oxide radicals. Total phenolic content of the plant extracts showed close correlation with the antioxidant activities, suggesting that phenolic compounds present in the plants may be a major contributor of the observed antioxidant activities. In conclusion, the methanol extract of A. occidentale can be an alternative source of polyphenolics with potent antioxidant activities.